1980
DOI: 10.1139/b80-178
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic studies in the Saxifragaceae s.l. 15. The flavonoids of subsection Villosae section Heuchera in the genus Heuchera

Abstract: The flavonoid constituents of Heuchera villosa var. villosa, H. parviflora var. parviflora, and H. glabra have been studied. The predominant flavonoids present in all three species were mono-, di-, and triglycosides of kaempferol, quercetin, and myricetin. Isorhamnetin, larycitrin, syringetin, and luteolin were also seen in some species. Dihydromyricetin was isolated from H. villosa. The data were compared with results obtained earlier from H. micrantha var. diversifolia and H. cylindrica. The hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Dendroseris appears to be an example where reduction in flavonoid chemistry has occurred during evolution, and contrasts with the reverse situation found in Robinsonia (Pacheco et al, 1985) where evolution seemingly has been accompanied by elaboration of the flavonoid profile mainly by accumulation of intermediate metabolites in flavonoid biosynthesis. This pattern has been shown in other genera, with the study of Heuchera by Wells and Bohm (1980) being a particularly compelling example. This pattern has been shown in other genera, with the study of Heuchera by Wells and Bohm (1980) being a particularly compelling example.…”
Section: Discussionmentioning
confidence: 60%
“…Dendroseris appears to be an example where reduction in flavonoid chemistry has occurred during evolution, and contrasts with the reverse situation found in Robinsonia (Pacheco et al, 1985) where evolution seemingly has been accompanied by elaboration of the flavonoid profile mainly by accumulation of intermediate metabolites in flavonoid biosynthesis. This pattern has been shown in other genera, with the study of Heuchera by Wells and Bohm (1980) being a particularly compelling example. This pattern has been shown in other genera, with the study of Heuchera by Wells and Bohm (1980) being a particularly compelling example.…”
Section: Discussionmentioning
confidence: 60%
“…Mabry (1974) suggested that within genera the more advanced species tend to have both fewer flavonoid compounds and structurally more sim-ple compounds. This pattern has been shown in other genera, with the study of Heuchera by Wells and Bohm (1980) being a particularly compelling example. In other genera, a trend toward greater flavonoid complexity seems to be the case, while in still other genera there appears to be no trend in either direction (Pacheco et al, 1985).…”
Section: Discussionmentioning
confidence: 60%
“…The monoglycosides identified were kaempferol, quercetin, and myricetin-3-0glucosides, their corresponding gallic acid conjugates, kaempferol and quercetin-3-0-arabinosides, xylosides, and rhamnosides, and the 7-0-glucoside of the flavanone naringenin. The position of attachment of the gallic acid residue on the flavonol glucosides was not firmly established, but the compounds had the same thin layer chromatographic and color behavior as the 6"-gallyl derivatives of the flavonol glucosides seen in Tellima grandiflora by Collins and coworkers (14) and in Heuchera species by Wilkins and Bohm (15) and Wells and Bohm (16). Kaempferol, quercetin, and ombuin-3-O-rhamnosylglucosides (probably the rutinosides) occurred along with a small amount of a quercetin-3-O-diglucoside whose structure was not pursued.…”
Section: Resultsmentioning
confidence: 98%